Macromedia Flash 8 [electronic resource] : interactive movie tutorials, starter - 172899 Shuman, James E. author (New York : Thomson Course Technology, 2007)
Add a new dimension to teaching Macromedia Flash 8 with this Cool School interactus movie tutorial CD! Cool School interactus products offer a unique learning environment that brings design concepts and techniques to life. Students watch as a professional takes them through essential software techniques, enabling them to put skills to immediate use.